Implementation of Recycling System in Graphic Industry to Reduce Environmental Pollution - Juwairiah, Juwairiah; Sinambela, Yusnia; Sitorus, Nurianti; Gobal, Raju (ABEC Indonesia, 2024)
he increase in production and consumption in the graphic industry has had a negative impact on theenvironment, especially related to the waste produced. Solid, liquid, and gas waste produced by this industry, includingwaste paper, chemicals, and emissions from the printing process, contribute to air, land, and water pollution. This studyaims to analyze the implementation of an effective recycling system in the graphic industry as an effort to reduceenvironmental pollution. The research method used is a case study in several graphic companies that have adopted arecycling system, focusing on the paper recycling process, the use of environmentally friendly inks, and chemical wastemanagement. Data were collected through interviews, field observations, and document analysis related to companypolicies and environmental audit results. The results of the study show that the implementation of an integrated recyclingsystem can reduce waste volume by up to 60%, increase the efficiency of raw material use by up to 30%, and significantlyreduce carbon emissions from the production process. In addition, companies that implement a recycling system also getadditional benefits in the form of savings in production costs and an improved environmentally friendly image in the eyesof consumers. This study concludes that the implementation of a holistic recycling system in the graphic industry is astrategic step to reduce negative impacts on the environment and encourage more sustainable business practices.